Metal-free direct oxidative C-C bond coupling of pyrazolones and quinoxalinones - Saowanee Toonchue (2019)
© the Partner Organisations 2018. A highly efficient transition metal-free oxidative chemo- and regioselective C-C bond coupling of pyrazolones and quinoxalinones mediated by K2S2O8 is described. This reaction can be conveniently carried out under mild conditions and gives various hydroxy-pyrazolyl quinoxalinone products in moderate to excellent yields in a short reaction time.